(NmAGNITNAQ MODELX LITOSFERY eWROPY (B/s - (NpA[KEWI^(B, (NiNNA kONSTANTINOWNAs; (NmARKOWSKIJ(B, (Nw(B.(Ns(B.s; (NoRL@K(B, (Nm(B.(Ni(B.s; (NkARATAEW(B, (NgERMAN iWANOWI^s; (NiNSTITUT GEOFIZIKI IM(B. (Ns(B.(Ni(B. (NsUBBOTINA an ussrs ((NkIEW (B:s (NnAUK(B. (NDUMKA(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 149-157 (236 (NNAZW(B.)s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NmAGNITNOE POLE zEMLIs; (NmODELIs